1990
DOI: 10.1099/00221287-136-2-327
|View full text |Cite
|
Sign up to set email alerts
|

Protective activity of glycolipid antigen against infection by Leptospira interrogans serovar canicola

Abstract: A protective glycolipid antigen (PAg) was extracted from Leptospira interrogans serovar canicola with chloroform/methanol/water (1 : 2: 0.8, by vol.) and partially purified by silica gel column chromatography. The PAg elicited a protective response in hamsters and in cyclophosphamide-treated mice subsequently challenged with homologous Lepfospira. The PAg band was detected as a single smear-like band, corresponding to a protein of 23-30 kDa, by silver-staining in SDS-PAGE. In immunoblots, this band reacted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(32 citation statements)
references
References 12 publications
0
30
2
Order By: Relevance
“…The majority were found to be localized in the LPS-like component of the cell. Ono [7], Masuzawa [8], and Schoone [9] reached similar conclusions and identified serovar-specific epitopes within the groups Canicola and Icterohaemorrhagiae.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The majority were found to be localized in the LPS-like component of the cell. Ono [7], Masuzawa [8], and Schoone [9] reached similar conclusions and identified serovar-specific epitopes within the groups Canicola and Icterohaemorrhagiae.…”
Section: Introductionmentioning
confidence: 55%
“…Two or three serum samples were sequentially obtained from six patients who became infected through drinking contaminated water [15]. They have been indicated with the arabic numbers 1, 7,8,9,12,17. Samples were collected: (a) immediately; (b) 18 months; and (c) 36 months after the epidemic outbreak.…”
Section: Human Seramentioning
confidence: 99%
“…We have isolated the protective antigen (PAg) from lyophilized whole cells and the outer-envelope fraction of L. interrogans serovar lai, copenhageni, canicola, autumnalis, hebdomadis and australis by chloroformmethanol-water extraction. We reported that PAg protected hamsters from experimental infection of homologous serovar (12,14,15). Furthermore, PAgs showed no endotoxic activities and the biological safety of PAgs as vaccine has been demonstrated (13).…”
Section: Introductionmentioning
confidence: 99%
“…PAg was extracted from lyophilized cells with a chloroform-methanol-water (1:2:0.8, v/v/v) solution (5) described previously (12,14). Samples (1 mg/ml) of PAg were suspended in 2 M formic acid and heated at 100 C for 2 hr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation